Genetic Diversity, Structure, and Selective Sweeps in Spinacia turkestanica Associated With the Domestication of Cultivated Spinach - Gyawali, Sanjaya; Bhattarai, Gehendra; Shi, Ainong; Kik, Chris; du Toit, Lindsey J. (Frontiers in Genetics, 2021)
Genotype-by-sequencing (GBS) was used to explore the genetic diversity and structure of Spinacia turkestanica, and the selective sweeps involved in domestication of cultivated spinach, S. oleracea, from S. turkestanica. A total 7,065 single nucleotide polymorphisms (SNPs) generated for 16 Spinacia oleracea and 76 S. turkestanica accessions placed the S. oleracea accessions in one group, Q1, and the 76 S. turkestanica accessions, which originated from Central Asia, in two distinct groups, Q2 and Q3. The Q2 group shared greater genetic identity with the S. oleracea accessions, Q1, than the Q3 S. turkestanica group,. Likewise, the S. oleracea Q1 group had a smaller Fst (0.008) with the Q2 group than with the Q3 group (Fst = 0.012), and a greater gene flow (Nm = 30.13) with the Q2 group than with the Q3 group (Nm = 21.83). The Q2 accessions originated primarily from Uzbekistan while the Q3 accessions originated mostly from Tajikistan. The Zarafshan Mountain Range appears to have served as a physical barrier that largely separated members of the Q2 and Q3 groups of S. turkestanica. Accessions with admixtures of Q2 and Q3 were collected primarily from lower elevations at the southern end of the Zarafshan Mountain Range in Uzbekistan. Selective sweep regions identified at 32, 49, and 52 Mb on chromosomes 1, 2, and 3, respectively, appear to have played a vital role in the domestication of S. oleracea as they are correlated with important domestication traits, including day length sensitivity for bolting (flowering). High XP-CLR scores at the 52 Mb genomic region of chromosome 3 suggest that a selective sweep at this region was responsible for early differentiation of S. turkestanica into two groups in Central Asia.